Nyctalus noctula Schreber 1774 - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2019)
15. Common Noctule Nyctalus noctula French: Noctule commune / German: Grof 3er Abendsegler / Spanish: Néctulo mediano Other common names: Noctule, Noctule Bat Taxonomy. Vespertilio noctula Schreber, 1774, France. Nyctalus noctula is sister to the clade including N. lasiopterus and N. aviator. N. plancyi has sometimes been included within this species, but is here recognized as a full species. The name labiatus has been moved to N. plancy: because of the clear morphological differences between N. noctula and labiatus, although labiatus has not been properly compared with N. plancyi; further research is required. Three subspecies recognized. Subspecies and Distribution. N. n. noctula Schreber, 1774 — throughout Europe from Great Britain, France, and Spain E to W Russia, W Kazakhstan, and SW Turkmenistan, including S Scandinavia, Gotland and Oland Is, and Cyprus (Cyprus records somewhat tentatively regarded as this subspecies). Absent throughout much of Iberia and is locally extinct in Portugal. N. n. lebanoticus D. L. Harrison, 1962 — WC & SW Syria, Lebanon, and NE Israel. N. n. mecklenburzevi Kuzyakin, 1934 — SC & E Kazakhstan, SC Russia, W Uzbekistan, Tajikistan, Kyrgyzstan, and NW China (Xinjiang). The species may be present in N Africa, with two records claimed from Algeria in 1858, but these may represent N. lasiopterus; further sampling is needed. Descriptive notes. Head-body 60-89 mm, tail 40-66 mm, ear 16-21 mm, hindfoot 12-14 mm, forearm 47-60 mm; weight 17-44 g. Dorsal pelage of the Common Noctule is a distinctive reddish brown (individual hairs unicolored), while ventral pelage is slightly paler. Juveniles and freshly molted adults are duller brown throughout. Ventral pelage extends onto wings and interfemoral membrane, as in other noctules. Face, ears, and membranes are dark brown, and tail extends a few millimeters past the uropatagium. Muzzle is short, with large glands between nostrils and eyes, and ears are short and triangular, with 4-5 folds on outer edge. Tragus is very short and ...